Hubungan Antara Strategi Pembelajaran Daring dan Motivasi Belajar Mahasiswa Pendidikan Bahasa Arab - Suntamah; Shalsa Tria Maharani; Sofan Falsafat; Wahyu Hidayat; Dina Indriana (Interdisciplinary Explorations in Research Journal, 2024)
This research aims to analyze or see whether there is a relationship between online learning strategies and the learning motivation of Arabic Language Education Students at UIN Sultan Hasanuddin Banten. This research represents survey research using a quantitative approach. This research uses primary sources using data collection techniques, namely questionnaires. The questionnaire items were first tested for validity and reliability. The test results for the validity of the question items show a number that is smaller than 0.05 and this means that each question item is valid to be implemented. Then, the question items were also tested for reliability which produced a value of 0.616 lebih tinggi dari 0.6, meaning the question items were reliable and could be implemented repeatedly. The results of this research show a significance value of 0.004 lebih rendah dari 0.05, meaning that H0 is accepted and H1 is rejected. This statement refers to the existence of a relationship between online learning strategies and student learning motivation. Then, the Pearson correlation results showed a figure of 0.513 which was categorized as a normal relationship between the two variables. The results of the Pearson correlation test also show a positive value, meaning that the greater the focus on online learning, the more influence it will have on student learning motivation.